RESERVOIR DISTRIBUTION MODELING OF X, Y AND Z SANDSTONES WITH HIGH RESOLUTION SEQUENCE STRATIGRAPHIC OF BEKASAP FORMATION, PANDORA FIELD CENTRAL SUMATRA BASIN - Hendro Heru Nugroho, Dwi
Pandora field is one of the oldest hydrocarbons producing fields in the Central Sumatra Basin, Indonesia. This field has several reservoir zones with a variety of hydrocarbon production rates. Reservoir models that have been using the correlation of sand to sand in the Pandora Field is not sufficient to explain the deposition of a more detailed facies in the X, Y and Z sandstones reservoir. Therefore, a redefinition of the reservoir rocks and geological understanding of the realistic conditions of the reservoir rock, geometry, facies distribution, and deployment of reservoir quality in order to provide guidance for the next development. The purpose of this study was to determine the model facies distribution and reservoir properties of X, Y and Z Sands of Bekasap Formation and depositional environment through a high-resolution sequence stratigraphic method. Validated with cores data descriptions and FMI logs, a distribution map of gross reservoir facies unit, a distribution of reservoir properties in the term of an effective porosity (isoporosity maps) and isopermeability maps. This study uses five data description of cores, two FMI log, 99 ELAN petrophysical and well logs data in the form of gamma ray, resistivity, neutron, sonic and density from 137 wells. Based on detailed sandstone reservoirs core descriptions of Bekasap Formation, can be identified that the three of X, Y and Z sandstones reservoirs have divided in two different facies deposition associations, the X sand reservoir facies as cross-bedded coarse-conglomeratic sandstone (meandering channel), while the reservoir facies Y and Z are blocky cross-bedded very coarse-conglomeratic sandstone-conglomerate (distributary channel). Both the deposition of these facies associations are interpreted as a tide dominated estuarine. Based on the results for the reservoir quality review of effective porosity and permeability for each facies association, suggesting that X is deposited on the sandstone tidaly meandering channel reservoir quality is relatively better than the Y and Z sandstones which are deposited on tidaly distributary channel.